Enhancing Cognitive, Performance Skills, and Affective Competencies through Case-Based Learning among Midwifery Students: A Scoping Review - Jelsita Nova; Ari Indra Susanti (Jurnal Ilmu Pendidikan dan Pembelajaran, 2026)
Midwifery students are expected to develop good clinical competencies to ensure the delivery of safe, effective, and holistic maternal care. However, conventional learning methods often fall short in cultivating critical thinking, clinical reasoning, and decision-making skills. Case-Based Learning (CBL) has emerged as a student-centered pedagogical strategy that bridges the gap between theory and clinical practice. This study aims to map the forms of CBL implementation in midwifery education, particularly in enhancing students’ competencies in cognitive, performance skills, motivational, and collaborative domains, while also highlighting contextual limitations in its application. This scoping review adopted the PRISMA-ScR framework and conducted searches across PubMed, ScienceDirect, and Google Scholar. Eligible articles were published between 2020 and 2025, written in English, and presented original full-text research. Out of 655 initially retrieved records, 12 studies met the inclusion criteria after title, abstract, and full-text screening. Findings show that CBL positively contributes to the development of midwifery students’ cognitive competencies, including critical thinking, knowledge retention, and clinical reasoning, as reported in the majority of studies. Improvements in performance skills, such as decision-making and practical readiness, were also noted, particularly when CBL was supported with technology like video-based scenarios and virtual reality. Additionally, CBL fostered student engagement, motivation, and collaboration, although one study reported limited enthusiasm due to contextual factors such as passive delivery. In conclusion, CBL is an effective pedagogical approach for developing cognitive, performance skills, and affective competencies in midwifery students. To optimize its impact, educators should integrate CBL with interactive digital tools such as simulation and virtual reality. These innovations enhance engagement and provide immersive learning experiences that align with the demands of reflective, hands-on maternal care. The findings of this review have important implications for midwifery education, particularly in supporting the adoption of more student-centered and clinically oriented teaching strategies to strengthen students’ competence and readiness for professional practice. Further research is needed to standardize CBL implementation and explore its long-term outcomes across diverse learning environments.